Upaya Peningkatan Bahasa Inggris di Kampung Wowara, Waimangura - Wilhelmina Kurnia Wandut; Silvester Nusa (Unram Journal of Community Service, 2022)
This Community Service aims to provide English assistance for children domiciled in Wowara village which is one of the villages in Southwest Sumba regency. This community service is made based on the concerns of the Implementer to children who are quite difficult in getting English learning at the elementary level. In addition, the progress of the tourism industry on the island of Sumba demands that it has ready human resources. In this community service process, an English learning group was formed that was divided into small groups and is expected to continue to be sustainable. The results of this process show that children who are in elementary school have an interest and motivation to learn English. In addition, they have also been equipped with basic English knowledge that will support their academics when they continue to the Junior High School stage